Social Environmental Support in Encouraging Entrepreneurial Behavior of Millennial Farmers in the Special Region of Yogyakarta, Indonesia: An Effort to Realize Sustainable Agriculture - Raden Rara Aulia Qonita; Masyhuri Masyhuri; Jamhari Jamhari; Hani Perwitasari (Universitas Sebelas Maret, 2025)
Sustainable agriculture offers new hope in overcoming the challenges of the decreasing interest of the younger generation in the agricultural sector. Millennial farmers, as part of this younger generation, are the key to successfully implementing sustainable agricultural development. This study aims to explore the influence of the role of parents, friends, extension workers, and media exposure on the entrepreneurial behavior of millennial farmers, and to explore the influence of entrepreneurial behavior on the financial performance of millennial farmers. The research was conducted in the Special Region of Yogyakarta, Indonesia, which was the first province to inaugurate 1,000 millennial farmers. The research sample consisted of 200 millennial farmers, selected using a simple random sampling method. The analysis employed Partial Least Square Structural Equation Modeling (PLS-SEM). The results reveal that the role of parents does not significantly influence millennial farmers’ entrepreneurial behavior. The role of friends, agricultural extension workers, and media exposure significantly influence millennial farmers’ entrepreneurial behavior. Friends provide motivation, support, and share information. Agricultural extension workers offer knowledge transfer, technology, and programs from the government. Media exposure contributes by providing knowledge and shaping perceptions and behavior. Entrepreneurial behavior has a positive and significant influence on financial performance. The research results impact millennial farmers’ regional commissariat/farmer groups, the extension services by agricultural extension workers, and the media for millennial farmers. It is recommended that policies be implemented to strengthen the role of the regional commissariat of millennial farmers/farmer groups, improve extension services, and develop media relevant to millennial farmers.